Normal pathogen-specific immune responses mounted by CTLA-4-deficient T cells: a paradigm reconsidered. - Bachmann, M; Gallimore, A; Jones, E; Ecabert, B; Acha-Orbea, H; Kopf, M (2001)
CTLA-4 is a critical negative regulator of T cell responses and CTLA-4-deficient (CTLA-4(-/-)) mice die of a lymphproliferative disease. Nevertheless, RAG-2-deficient mice reconstituted with a mixture of CTLA-4(-/-) and normal (CTLA-4(+/+)) bone marrow survive in the absence of any signs of disease, although 50% of their T cells do not express CTLA-4. Using such mixed chimeras, we analyzed the role of CTLA-4 in specific T cell responses to lymphocytic choriomeningitis virus, Leishmania major and mouse mammary tumor virus, which cause acute, chronic and persistent infections, respectively. The populations of antigen-specific CTLA-4(-/-)CD4(+) and CTLA-4(-/-)CD8(+) T cells became activated, expanded and contracted indistinguishably from CTLA-4(+/+)CD4(+) and CTLA-4(+/+)CD8(+) T cells after infection with all three pathogens. Thus, CTLA-4 is not involved in the down-regulation of specific T cell responses and peripheral deletion in a T cell-autonomous fashion.